T helper cell infiltration in osteoarthritis-related knee pain and disability - Nees, Timo A.; Rosshirt, Nils; Zhang, Jiji A.; Platzer, Hadrian; Sorbi, Reza; Tripel, Elena; Reiner, Tobias; Walker, Tilman; Schiltenwolf, Marcus; Lorenz, Hanns-Martin; Tretter, Theresa; Moradi, Babak; et al. (Journal of Clinical Medicine, 2020)
Despite the growing body of literature demonstrating a crucial role of T helper cell (Th) responses in the pathogenesis of osteoarthritis (OA), only few clinical studies have assessed interactions between Th cells and OA—related symptoms. Yet, the inclusion of clinical data in the interpretation of cellular analyses of Th cell infiltration is essential to reveal the mechanisms underlying the complex pathophysiology of OA pain and disability. Thus, the aim of the study was to analyze the infiltration pattern of Th cells in systemic (peripheral blood) and joint-derived (synovial membrane and fluid) samples from patients with knee OA in relation to OA-induced pain and disability. Therefore, radiographic OA severity, knee pain and function of 47 OA patients undergoing knee arthroplasty were evaluated prior to surgery. In parallel, samples of peripheral blood (PB), synovial membrane (SM) and synovial fluid (SF) were harvested and analyzed for different Th subsets using flow cytometry. According to surface marker expression Th cells (CD3+ CD4+ CD8−) were assigned to the Th subsets Th1 (CXCR3+, CCR5+), Th2 (CCR3+, CCR4+) and Th17 (CD161+, CCR6+). Interestingly, infiltration of the SM with all Th subtypes (Th1, Th2, Th17) significantly correlated with OA-induced disability. Most importantly, synovial CCR5+ and CCR3+ Th cell infiltration was associated with OA-related knee pain and disability. Furthermore, higher percentage rates of CXCR3+ Th cells in all tissue samples (PB, SM, SF) showed significant associations with OA severity. In contrast, increasing percentage rates of CD161+ Th cells in SM samples corresponded to a better functional outcome. In conclusion, the current study provides an extensive profile of the Th cell infiltration pattern in PB, SF and SM from patients with clinically relevant knee OA. Th cell infiltration of the SM might play a crucial role not only in the pathogenesis of OA but also in the development of OA-related knee pain and disability.